Documental sobre los molinos artesanales de Latacunga como símbolo de identidad cultural - Corrales Castellano, Daniela Silvana (2016)
The present research work aim is to investigate the history of traditional mills in Latacunga theseare: (Molinos Monserrat, Molinos Poultier, Molinos Villacreses, familia Vascones y la familia Parra), because these were the pioneers in starting this milling activity in the city, taking advantage of the flow of different rivers that through the city. The milling activity was gaining strength, and that is why this activity was expanding to other parts of the city like San Felipe and Brazales. The themes in this study were generated regarding traditional mills (anecdotes, experiences, stories and economy) because people in Latacunga city are known by the nickname "mashcas", this term comes from barley flour toast and many years ago people in the city made this product the main food of their daily diet. Through this research it was evident the little information and studies that exist on traditional mills, relative to other countries that have information on it, and until there is a specific date which marks the national day of the mill, as is the case of the Netherlands held the second Saturday of May each year. The completion of this work determined that traditional mills today are beginning to disappear for various reasons (natural disaster, lack of operating license, lack of spare parts for mills and forgetting people) causing little importance on these.The purpose of this research is to make a documentary about the traditional mills, revealing their history and the importance of it, creating a striking audio visual product where people can learn and educate their self about the traditional mills.